1997
DOI: 10.1046/j.1365-2273.1997.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between obstructive sleep apnoea and body mass index

Abstract: Obese patients have a high prevalence of obstructive sleep apnoea (OSA), but a low response rate and high frequency of relapse after uvulopalatopharyngoplasty (UVPP). In this study we have determined the level of obstruction during sleep in 31 men with OSA, using a catheter with multiple micropressure transducers and a portable digital recorder. The proportion of apnoeic episodes with obstruction at lower levels correlated with increasing body mass index (BMI) (P < 0.05). Thus, with increasing obesity, there s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…The prevalence of SDB among the bus drivers was much higher than our first year university students 9 and this was most likely related to the effects of age and higher BMI among the bus drivers. BMI, an independent predictor of RDI in this study, has a clearly established relationship with OSA 32−34 . Several studies have shown that cardiovascular morbidity occurs in Asian people who have a lower BMI than the current World Health Organization (WHO) cut‐off used to define an increase in morbidity among adult Caucasians, and that Asians tend to accumulate intra‐abdominal fat without developing generalized obesity 35,36 .…”
Section: Discussionmentioning
confidence: 50%
“…The prevalence of SDB among the bus drivers was much higher than our first year university students 9 and this was most likely related to the effects of age and higher BMI among the bus drivers. BMI, an independent predictor of RDI in this study, has a clearly established relationship with OSA 32−34 . Several studies have shown that cardiovascular morbidity occurs in Asian people who have a lower BMI than the current World Health Organization (WHO) cut‐off used to define an increase in morbidity among adult Caucasians, and that Asians tend to accumulate intra‐abdominal fat without developing generalized obesity 35,36 .…”
Section: Discussionmentioning
confidence: 50%
“…The different patterns of pharyngeal collapse as described by Fujita (Fujita I, II and III) are covered by a single term, which accurately describes the distribution of obstructive events (for further clarification see Table 1). This descriptor that enables analysis of continuous data can also be used to define the main site of obstructive events being either > 50% upper of all obstructive events corresponding to mainly upper or < 50% corresponding to mainly lower obstructive events (of all) [12,13]. The upper site ideally corresponds to the aim of common surgical augmentation such as UPPP.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, most patients with OSA may be described as having a distribution of obstructive events corresponding to Fujita type II: a mixture of transpalatal and subpalatal. As a consequence, we have introduced the term: "percent upper" [percentage transpalatal of all (transpalatal+subpalatal)] obstructive events to describe the distribution of obstructive events [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In adults, the most known risk factor for SDB, and one of the first described in adults and animals, is obesity. [5][6][7][8][9][10] It may also be a risk factor in adolescents and children as well. However, there are very few data on obesity as a risk factor for SDB in children and adolescents.…”
Section: Methodsmentioning
confidence: 99%